2017
DOI: 10.1177/1075547017738018
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Public Engagement Outcomes by the Use of an Outcome Expectations Scale for Scientists

Abstract: This study presents initial work to validate a scale designed to measure scientists’ outcome expectations in relation to public engagement. A 20-item survey was administered to a sample of 341 scientists. Graded response models were used to assess the quality of the items. Results suggest that six items provided the strongest measure of outcome expectations, with classically adequate reliability across a wide range of scientists and scores. The findings are presented in relation to the short-term outcomes of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 21 publications
0
18
0
Order By: Relevance
“…Further research has focused on helping scientist-communicators improve and assess their self-efficacy (Robertson Evia, Peterman, Cloyd, & Besley, 2018) and reflect on their efforts and goals to encourage EOC approaches that emphasise "reciprocal exchanges" between scientists and publics (Peterman, Robertson Evia, Cloyd, & Besley, 2017). These exchanges are thought to increase connectedness between scientists and the communities or publics with whom they interact through their EOC efforts (e.g.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Further research has focused on helping scientist-communicators improve and assess their self-efficacy (Robertson Evia, Peterman, Cloyd, & Besley, 2018) and reflect on their efforts and goals to encourage EOC approaches that emphasise "reciprocal exchanges" between scientists and publics (Peterman, Robertson Evia, Cloyd, & Besley, 2017). These exchanges are thought to increase connectedness between scientists and the communities or publics with whom they interact through their EOC efforts (e.g.…”
mentioning
confidence: 99%
“…These exchanges are thought to increase connectedness between scientists and the communities or publics with whom they interact through their EOC efforts (e.g. Mayhew & Hall, 2012;Peterman et al, 2017) and is another way to describe dialogue-driven approaches. As an example, Peterman et al (2017) developed an Outcome Expectancy Scale, a new evaluation scale intended to help measure "outcome expectations" for both scientists and publics engaged in EOC activities.…”
mentioning
confidence: 99%
“…Some focus on public engagement with science and, specifically, the outcomes of volunteer citizen scientists (e.g., the Developing, Validating and Implementing Situated Evaluation Instruments [DEVISE] scales; Cornell Lab of Ornithology, ); others target constructs such as the “activation” of science learning that can bridge formal and informal contexts (Activation Lab, ). Most recently, the American Association for the Advancement of Science commissioned the development of shared measures for scientists who participate in public engagement activities (Peterman, Robertson Evia, Cloyd, & Besley, in press; Robertson Evia, Peterman, Cloyd, & Besley, ).…”
Section: Looking Aheadmentioning
confidence: 99%
“…Correlational studies have shown that scientists who engage with the public also perform better academically (26,27). Web 2.0 provides scientists with platforms to directly disseminate their scientific messages, and allows broad audiences to comment, react, and potentially engage in dialogue with scientists (2,6,28,29).…”
Section: Rationalementioning
confidence: 99%